Purification of glutathione Transferases (GSTs) from identified Rhizospheric bacteria - Khanom Simarani,; Wan Haizatul Akmal Che Yusoff,; Zazali Alias, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The glutathione S-Transferase (GST) enzyme plays an important role in cellular detoxification. This multifunctional enzyme is involved in Phase II detoxification pathways that protect cellular macromolecules from being attacked by harmful compound. The study is an attempt to isolate glutathione transferase-expressing bacteria from the rhizospheric soil of selected herbal plants. Screening showed nine positive isolates out of twelve bacterial samples from a large microbial population in our soil collection. Crude extract from strain E1 which was isolated from Piper sarmentosum (Kadok) showed the highest specific activity against 1-chloro-2, 4-dinitrobenzene substrates (5.78 × 10-06 μmol/min/mg). Based on the carbon utilization of E1 assessed using Biolog system, the strain was identified as Comamonas testosterone E1. Glutathione S-transferase purification using GST trap yielded two distinct subunits with molecular weights of 23 and 24 kDa as visualized on 1D SDS-polyacrylamide gel electrophoresis. The purified GST showed reactivity towards 1-chloro-2, 4-dinitrobenzene, 1, 2-dichloro-4-nitrobenzene and ethacrynic acid with specific activity of 0.264 ± 0.038 nmol/min/mg and 0.056 ± 0.002 nmol/min/mg and 10.500 ± 3.130 nmol/min/mg, respectively. However, no activity was detected against p-Nitrobenzyl chloride, Sulfobromophthalein, trans-4-phenyl-3-butene-2-one, hexa-2, 4- dienal, trans-hepta-2, 4-dienal and trans-oct-2-enal in the study.